Secrecy, sabotage, and aiding the resistance : how Anglo-American co-operation shaped World War Two. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2018)
When the British and American security services went to war together, their targets included morale, supplies and governments. Sabotage training and supplying rebels in occupied countries weakened the enemy. Friends were found in Italy and hostile groups in America. The American OSS and British SOE would also deliberately keep some information from each other. When they did work together, companies in hostile countries were blacklisted and their covert Jedburgh units supported allied rebels around the world.
Date range: 1939-1954.
Keywords: World War, 1939-1945 -- Diplomatic history; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- 1936-1945.